2020
DOI: 10.1177/0093650220952231
|View full text |Cite
|
Sign up to set email alerts
|

The Indirect Effects of Thinspiration and Fitspiration Images on Young Women’s Sexual Attitudes

Abstract: Applying the sociocultural theory and the objectification theory, this experiment examined the indirect effects of inspirational Instagram images (i.e., fitspiration and thinspiration) on young women’s sexual attitudes. A post-test only between-subjects design with three experimental conditions (i.e., fitspiration, thinspiration, and control images) was conducted with female college students ( N = 221). The results supported the sociocultural theory, revealing that viewing inspirational Instagram images led to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Basically, fitspiration is a combination of two words "fitness" and "inspiration" that is created to encourage the audience to exercise regularly and eat healthy foods (Fordouly & Vartanian, 2019). On the other side, thinspiration is a combination of "thinness" and "inspiration" which aims to inspire the audience to have a slim body like idealized beauty standards (Chansiri et al, 2020). Refers to research by Chansiri et al (2020), watching fitspiration content on Instagram affects the audience's low self-esteem, and they tend to compare their own body with the body depicted in its social media.…”
Section: Literature Review the Influence Of Media Exposure Towards Bo...mentioning
confidence: 99%
“…Basically, fitspiration is a combination of two words "fitness" and "inspiration" that is created to encourage the audience to exercise regularly and eat healthy foods (Fordouly & Vartanian, 2019). On the other side, thinspiration is a combination of "thinness" and "inspiration" which aims to inspire the audience to have a slim body like idealized beauty standards (Chansiri et al, 2020). Refers to research by Chansiri et al (2020), watching fitspiration content on Instagram affects the audience's low self-esteem, and they tend to compare their own body with the body depicted in its social media.…”
Section: Literature Review the Influence Of Media Exposure Towards Bo...mentioning
confidence: 99%
“…Following the experimental manipulation, participants are asked to complete post-test measures of body image-related constructs. Three studies (Chansiri et al, 2020;Kim, 2020;Veldhuis et al, 2014) assessed the experimental effect of viewing idealized SNS images using post stimulus scores only. Finally, in pretest and posttest within subject studies (Alanazi et al, 2019;Krug et al, 2020;Yee et al, 2020) participants complete the baseline assessments of body imagerelated constructs, and then they are randomly exposed to all the different conditions (i.e., idealized and control images).…”
Section: Types Of Experimental Designmentioning
confidence: 99%
“…Usually they included full-body shots of women with thin physiques either posing in bikinis, form-fitting fashion, and revealing outfits to emphasize their body shape. In four studies (Alanazi et al, 2019;Chansiri et al, 2020;Taniguchi & Lee, 2012, 2013Veldhuis et al, 2014) thin ideal images demonstrated women having an extremely thin body (i.e., visibly low body mass index), and photos were taken from angles that visually emphasized the model's thinness, particularly in terms of the model's arms, waist, and the gap between her thighs. Only one study (Brichacek et al, 2018) was conducted on a sample composed by both men and women, in this case men were exposed to viewing muscular/lean bodies.…”
Section: Thin Beauty Ideal Imagesmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also important to note the societal changes that have occurred since the publication of Calogero and Thompson's (2009a) study, including a profound increase in social media and dating app use among young adults (Pew Research Center, 2016, which likely has implications for their sexual self-concepts and behaviors (Chansiri et al, 2020;Hanna et al, 2017;Manago et al, 2015;Tomaszewska & Schuster, 2020). However, we used the same target measures as the original study, and both studies were conducted online.…”
Section: Replication Designmentioning
confidence: 99%